IIMPLEMENTASI KEBIJAKAN PEMBANGUNAN PARIWISATA DALAM PENINGKATAN SEKTOR USAHA MIKRO KECIL MENENGAH (UMKM) DI OBJEK WISATA PULAU MERAH KABUPATEN BANYUWANGI - Novitasari, Bella; ,S.Fil.,MA, Bandiyah; Wiwin Dwi Wismayanti, Kadek (CITIZEN CHARTER, 2015)
ABSTRACT Local Government of Banyuwangi Regency has a commitment in development activities of Pulau Merah tourists attraction by involving the micro, small, and medium business entities. The commitment is realized in programs that are empowering. Starting from the phenomenon, the author is interested in conducting this research to take the topic of “Implementation of Tourism Development Policy to Improve Micro, Small and Medium Business Sector (UMKM) in Pulau Merah tourists attraction Banyuwangi Regency. The general objective of this study was to see the picture of the implementation of tourism development policy to improve micro, small and medium business sector and to determine the successes and barriers that exist in practice. The methodology used in this study is qualitative descriptive. The theory used in this research is the Theory of Public Policy by using the Policy Implementation Model of George C. Edward III. To obtain the data, the author did an observation by directly looking at the phenomena that occurs in practice and conducted in-depth interviews with sources in association with the development policy to improve micro, small and medium business sector (UMKM) in Pulau Merah tourists attraction. From the findings of the research conducted, it can concluded that the policy is able to bring a positive impact, such as the community profession changeover and changing of its lifestyle. This policy is supported by programs which facilitate the development of UMKM, skills training, entrepreneurship, and skills, UMKM cooperative clinic, MOL from the Department of Koperasi and UMKM. However, at the stage of implementation, the policy is not optimal because it is collided with the readiness of the local government bureaucracy. Therefore, it is expected in the future that Local Government of Banyuwangi Regency makes a more detailed planning regarding of the path of coordination among regional organizations involved as well as human resources who execute the policy. Keywords: Policy Implementation, Tourism Development, Improving UMKM Sector, Pulau Merah Tourists Attraction